Koraki do zaupanja vredne (certificirane) ponudbe ekološke hrane v gastronomiji - Robačer, Martina; Vukmanič, Tjaša; Bavec, Franci; Bavec, Martina (2018)
Steps to a Trusted (Certified) Offer of Organic Food in Gastronomy. Tourism is one of the most important activities in the world and also in Slovenia, which should be closely connected with agriculture, as a custodian of cultivated landscapes with high biodiversity and a supplier of quality raw materials for food preparation, as well as with its culinary tradition and cultural heritage of the countryside. In recent years, one of the most important growing markets in tourism has been in the world, i.e. green tourism, ecotourism, sustainable tourism ... where different definitions and concepts appear, often self-declarating. Organic agriculture, which according to all criteria of sustainability (environment, society, economy) is the highest evaluated environmentally friendly agricultural production with the highest positioned quality food, can be a natural ally of "green" tourism, which is also promoted by the Republic of Slovenia (RS) . The internal quality of organically produced foods is different compared to conventional and / industrially produced foods, is controlled and certified and labeled in accordance with European legislation. The traceability of organic foods must also continue in gastronomy, which is covered by national legislation (Official Gazette of RS, No. 8/2014), which provides the legal basis for the procedures for control and certification in gastronomy, in all mass caterers.
Keywords: organic farming; organic foods; gastronomy; tourism; certified offer